Conditions and constraints of political participation among Turkish students in Germany - Frank Reichert (Cogent Psychology, 2017)
What motivates conventional and unconventional participation in the political realm? Specifically, what are the facilitators and constraints of political participation in the views of Turkish migrants? The present study explored these conditions using semi-structured interviews with a small number of university students of Turkish descent in Germany, as these may be more likely to become spokespersons of the Turkish people in Germany than other members of their ethnic minority in-group. The interviewees draw attention to characteristics of different kinds of political activities, linking them to a lack of trustworthiness, frustration, disappointment, and reflection. Most of these factors can be related to rational actor approaches of political behavior; hence, the findings are discussed with respect to rational choice theory and with regard to the importance of sociopolitical and emotional integration of Turkish migrants. The role of political trust is discussed as that of a potential moderating force in the facilitation of political participation.